1991
DOI: 10.1099/0022-1317-72-11-2661
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the influenza A virus PB2 protein in the regulation of viral gene expression

Abstract: To determine the function(s) of the PB2 protein of influenza A virus, six temperature-sensitive (ts) mutants of A/Udorn/72 (H3N2) virus, each carrying a ts mutation in the PB2 gene, were analysed for virus RNA and protein synthesis. One of the mutants, ICRC27, exhibited unique phenotypes and was characterized in detail. At the non-permissive temperature, 40 °C, the accumulation of mRNA for each genome segment was reduced severely, leading to delayed and reduced synthesis of viral proteins, complementary and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The vRNA/cRNA ratio of about 9:1 obtained for the wild-type promoter construct was expected, since synthesis of cRNA, a replicative intermediate, in most viral systems is substantially lower than that of vRNA synthesis. This result was similar to that obtained for influenza A virus, where a vRNA/ cRNA ratio of 10:1 was demonstrated (30). However, only a minor influence on the vRNA/cRNA ratio could be detected for the mutants tested.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The vRNA/cRNA ratio of about 9:1 obtained for the wild-type promoter construct was expected, since synthesis of cRNA, a replicative intermediate, in most viral systems is substantially lower than that of vRNA synthesis. This result was similar to that obtained for influenza A virus, where a vRNA/ cRNA ratio of 10:1 was demonstrated (30). However, only a minor influence on the vRNA/cRNA ratio could be detected for the mutants tested.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, the vRNA amplification product was easily detectable for all examined promoter mutants due to the RNA transcribed by RNA polymerase I. However, the amount of cRNA was much lower than that of the vRNA, as expected for a negative-strand RNA virus (30) (Fig. 5, upper panel).…”
Section: Vol 76 2002 Analysis Of the Uukuniemi Virus Promoter 10855supporting
confidence: 81%
“…In brief, viral proteins were separated by SDS-polyacrylamide gel electrophoresis as described before [41] and transferred to polyvinylidene difluoride membrane. After immobilization of the protein on the membrane, the membrane was blocked with 3% nonfat milk in TBS buffer at room temperature for 1 h and then treated with a 1∶10,000 dilution of the primary antibody (anti-Udorn antibody) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the PB2 subunit acts as an endonuclease in the generation of transcription primers (26), but the enzymatic activity requires the association of all three polymerase subunits and both template RNA ends (16), supporting the notion that the active viral ribonucleoproteins are in a panhandle structure (17). A number of reports have described the isolation and characterization of TS PB2 gene mutants (23,25,29,30,34,50,54). These mutants showed a block in mRNA synthesis and hence in virion RNA and protein accumulation, and one of the mutants described (34) showed an altered pattern of mRNA synthesis at the permissive temperature.…”
mentioning
confidence: 98%